Pengaruh Pembelajaran Kewirausahaan Dan Motivasi Kewirausahaan Terhadap Minat Menjadi Pengusaha Muda - Nurrahima Abdullah; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine the effect of entrepreneurship learning and entrepreneurship motivation on the interest in becoming a young entrepreneur. The research method used is quantitative with a survey approach. The sample in this study consisted of students who had taken entrepreneurship courses. The data analysis technique used multiple linear regression to test the simultaneous and partial effects between independent variables (entrepreneurship learning and entrepreneurship motivation) on the dependent variable (interest in becoming a young entrepreneur). The results of the study showed that both partially and simultaneously, entrepreneurship learning and entrepreneurship motivation had a significant effect on the interest in becoming a young entrepreneur.